ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN DI KEDAI KOPI HITAM MANIS BONTO BULAENG - Prihandoyo, C.; Dedy Deomedes, Stepanus; Hermawansyah, Adi (MEDIA RISET EKONOMI [MR.EKO], 2024)
The aim of this research is to analyze the Marketing Strategy of the Black Sweet Coffee Shop in increasing its sales volume amidst very tight competition using SWOT analysis, by identifying internal and external factors that influence marketing success. This research was conducted to determine the SWOT analysis carried out by Kedai Kopi Hitam Manis in carrying out the marketing mix and to determine marketing implementation in an effort to increase sales volume. The tool used is a qualitative approach which is classified as field research and in collecting data it uses observation, interviews and documentation methods. . Data analysis was carried out by reducing data, presenting data and drawing conclusions. The conclusions of this research show that in the implementation of SWOT at the Black Manis Bonto Bulaeng coffee shop, the strengths are the quality of the products produced, affordable prices, direct sales promotion through online media and strategic location in the middle of a densely populated residential area. Weaknesses include the difficulty of getting good quality human resources and limited parking space for visitors. In the opportunity there is a wide market share, increasing number of business places because drinking coffee has become part of people's lifestyle, but in the threat there is the emergence of new competitors who of course have new strategies that are much better. Apart from that, in its implementation, the marketing strategy to increase the sales volume of Kedai Kopi Hitam Manis Bonto Bulaeng carries out a product strategy by looking for cheap suppliers, a price strategy by making prices affordable, a place strategy by improving the facilities of the place that places music players and a promotion strategy using the word promotion method. of mouth and through social media.